Enhancement in energy storage performance of La-modified bismuth-ferrite-based relaxor ferroelectric ceramics by defect compensation and process optimization. Issue 22 (15th November 2022) - Yan, Yan; Zeng, Xinyu; Tang, Mingyang; Song, Simeng; Chen, Fukang; Wang, Yangyang; Yang, Lishun; Jin, Li; Liu, Gang
Abstract: In this investigation, La2 O3 was doped into 0.85(0.65BF-0.35BT)-0.15Sr0.7 Bi0.2 TiO3 (BF-BT-SBT) to form a solid solution with relaxation ferroelectric properties. The dielectric breakdown strength (BDS) of 1% mole of La doping was 220 kV/cm, the maximum recoverable energy storage ( W rec ) was 2.35 J/cm 3, and the energy storage efficiency ( η ) was 71%. The relationship between ceramic properties and microstructure was investigated in detail. Doping with La has the following main features: (1) The dissolution of La 3+ ions in the A position of the original perovskite structure reduced the concentration of oxygen vacancies in the lattice and played a role of compensating the defects. (2) The dielectric loss of ceramics was reduced, the impedance was greatly increased, and the specimen exhibited a high-temperature stability: a maximum W rec of 4.04 ± 1.7% J/cm 3 in 30–130 °C. (3) The core–shell–like with single phase structure in La-doped ceramics had been successfully observed, which may become a strategy for preparing high-performance ceramics. Higher BDS and denser structures were obtained in 0.01 La ceramics by further optimizing the preparation of the above compositions by the viscous polymer process (VPP). The BDS of 0.01La ceramics prepared by VPP reached 480 kV/cm, the effective energy storage density reached 6.15 J/cm 3, and the η was about 81%. This made La-doped 15SBT (chemical composition of BF-BT-SBT + La2 O3 ) ceramics become a potential candidate material for energy storage devices.